1980
DOI: 10.1038/283084a0
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory oscillations in arterial carbon dioxide tension as a control signal in exercise

Abstract: We have monitored oscillations in arterial pH (of respiratory frequency) in normal man at rest and during exercise. The pH oscillations are known to reflect respiratory oscillations in arterial carbon dioxide tension generated at the lungs. We have found that the pH oscillations increase in their upslope and downslope during exercise. This means that oscillations in arterial carbon dioxide tension can be considered as a control signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 2 publications
1
39
0
Order By: Relevance
“…The information which Yamamoto (1960) Band, Wolff, Ward, Cochrane & Prior (1980) showed, (at least for one subject), that this information can reach the arterial blood stream in the form of P.,co2 oscillations. The P. Co3 oscillation rate of change increased as expected from the alveolar gas studies reported here.…”
Section: Methodsmentioning
confidence: 99%
“…The information which Yamamoto (1960) Band, Wolff, Ward, Cochrane & Prior (1980) showed, (at least for one subject), that this information can reach the arterial blood stream in the form of P.,co2 oscillations. The P. Co3 oscillation rate of change increased as expected from the alveolar gas studies reported here.…”
Section: Methodsmentioning
confidence: 99%
“…When the first increase of breathing occurs around the third breath this assumption is no longer tenable, for dpH/dtjmax is a potential humoral signal at this time. Band et al (1980) have recorded a change in dpH/dt on the downstroke of the pH oscillation in the brachial artery of man by the second breath of exercise. This rapid development of a chemical signal in the arterial blood is presumably due to an abrupt increase in cardiac output at the start of exercise.…”
Section: Comparison Of the Present Experiments With Other 8tudie8mentioning
confidence: 99%
“…They found increases in the amplitude and the slope of pH oscillation (4pH/dt) with intravenous C02 administration while both amplitude and the slope decreased during C02 inhalation. It has also been shown in man using a left brachial artery cannula that during exercise both amplitude and the slope of pH oscillation increased with Vcp2 (BAND et al, 1980). CROSS et al (1982) found a logarithmic relationship between the maximum slope of the downstroke of pH oscillation ((d pH/dt)~mag) and V00, during on-transient of electrically induced exercise in the dog.…”
Section: Discussionmentioning
confidence: 99%